Review on gas-liquid mixing analysis in multiscale stirred vessel using CFD - Sajjadi, B.; Abdul Raman, Abdul Aziz; Ibrahim, Shaliza; Shah, R.S.S.R.E. (2012)
This review aims to establish common approaches and equations used in computational fluid dynamics (CFD) analysis for gas-liquid mixing operations and investigate their strengths and weaknesses. The review concluded that with a sufficient computing strength, Eulerian-Lagrangian approaches can simulate detailed flow structures for dispersed multiphase flow with high spatial resolution. Turbulence is an important factor in fluid dynamics, and literature confirmed that k- e is the most widely used turbulence model. However, it suffers from some inherent shortcomings that stemmed from the assumption of isotropy of turbulence and homogenous mixing, which is suitable for very high Reynolds number in unbaffled stirred vessels. In CFD simulations for gas-liquid systems in stirred vessels, bubble size distribution is the most important parameter; hence, different techniques for formulation of bubble size equations have been investigated. These techniques involve source and sink terms for coalescence or breakup and provide a framework in which the population balance method together with the coalescence and breakup models can be unified into three-dimensional CFD calculations. Different discretization schemes and solution algorithms were also reviewed to confirm that third-order solutions provide the least erroneous simulation results. Â© 2012 by Walter de Gruyter, Berlin, Boston.